Metabolic shifts toward glutamine regulate tumor growth, invasion and bioenergetics in ovarian cancer. Issue 5 (5th May 2014) - Yang, Lifeng; Moss, Tyler; Mangala, Lingegowda S; Marini, Juan; Zhao, Hongyun; Wahlig, Stephen; Armaiz‐Pena, Guillermo; Jiang, Dahai; Achreja, Abhinav; Win, Julia; Roopaimoole, Rajesha; Rodriguez‐Aguayo, Cristian; et al.
Abstract Glutamine can play a critical role in cellular growth in multiple cancers. Glutamine‐addicted cancer cells are dependent on glutamine for viability, and their metabolism is reprogrammed for glutamine utilization through the tricarboxylic acid (TCA) cycle. Here, we have uncovered a missing link between cancer invasiveness and glutamine dependence. Using isotope tracer and bioenergetic analysis, we found that low‐invasive ovarian cancer (OVCA) cells are glutamine independent, whereas high‐invasive OVCA cells are markedly glutamine dependent. Consistent with our findings, OVCA patients' microarray data suggest that glutaminolysis correlates with poor survival. Notably, the ratio of gene expression associated with glutamine anabolism versus catabolism has emerged as a novel biomarker for patient prognosis. Significantly, we found that glutamine regulates the activation of STAT3, a mediator of signaling pathways which regulates cancer hallmarks in invasive OVCA cells. Our findings suggest that a combined approach of targeting high‐invasive OVCA cells by blocking glutamine's entry into the TCA cycle, along with targeting low‐invasive OVCA cells by inhibiting glutamine synthesis and STAT3 may lead to potential therapeutic approaches for treating OVCAs.